2021
DOI: 10.1111/ppa.13409
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant health in the sustainable production of seed yams in Nigeria: A challenging nexus between plant health, human food security, and culture

Abstract: Yam (Dioscorea rotundata Poir) is a root and tuber crop throughout West Africa and has significant nutritional, economic and cultural value which underpin its importance for the food security of many people who live there. The crop is propagated vegetatively, primarily via the planting of small whole tubers (seed yams) and pieces (setts) cut from larger tubers.However, the use of such vegetative material means that a variety of pests (primarily insects and nematodes) and diseases (primarily fungal and viral) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…About 44% of the total genotypes assessed had ≤10% tuber weight loss, of which three belonged to D. rotundata (TDr 89/02565, TDr 98/03015 and TDr 99-15), three belonged to D. esculenta (MOSLY045-12, MOSLY047-12 and KESLY011-12), three belonged to D. cayenensis (BOSLY071-13, MOSLY051-12 and BOSLY056-12), four belonged to D. bulbifera (MOSLY023-12, MOSLY044-12, MOSLY024-12 and KESLY09-12) and 37 genotypes belonged to D. alata (comprising eight introduced and 29 landraces). Our findings agree with Morse et al [50], who reported that most of the yam rot induced by insect attacks is mainly due to storage beetles (Coleoptera sp. ), mealy bug (Planococcus citri) and scale insects (Aspidiella hartii) during storage.…”
Section: Effect Of Storage Disease Severity On Tuber Weightsupporting
confidence: 93%
“…About 44% of the total genotypes assessed had ≤10% tuber weight loss, of which three belonged to D. rotundata (TDr 89/02565, TDr 98/03015 and TDr 99-15), three belonged to D. esculenta (MOSLY045-12, MOSLY047-12 and KESLY011-12), three belonged to D. cayenensis (BOSLY071-13, MOSLY051-12 and BOSLY056-12), four belonged to D. bulbifera (MOSLY023-12, MOSLY044-12, MOSLY024-12 and KESLY09-12) and 37 genotypes belonged to D. alata (comprising eight introduced and 29 landraces). Our findings agree with Morse et al [50], who reported that most of the yam rot induced by insect attacks is mainly due to storage beetles (Coleoptera sp. ), mealy bug (Planococcus citri) and scale insects (Aspidiella hartii) during storage.…”
Section: Effect Of Storage Disease Severity On Tuber Weightsupporting
confidence: 93%
“…Defining the socio-cultural systems and determinants that structure the exchange or purchase of seeds and agricultural practices could help identify the economic and social constraints that influence the deployment of control strategies. An example is the use of yam clean seeds, which has encountered difficulties in West Africa through its adoption by farmers because it implies changes from traditional practices such as using tubers from the previous harvest as planting material [117].…”
Section: Epidemiology: Transmission Reservoir Plants and Cultural Pra...mentioning
confidence: 99%
“…Seed yam production using the minisett technology was introduced in Ghana and Nigeria [20], however, the small (25g) minisett size require special care and brings about yam tubers being often too small for planting as seed yams [21]. These are key obstacles to farmers towards adopting the technique [22]. A pre-harvest treatment may be defined as a system of existing technologies for agricultural raw materials production [23].…”
Section: Introductionmentioning
confidence: 99%